Organization’s Characteristics that Facilitate the Innovation Process and Techniques- Case of Oman - Matriano, Maria Teresa (Advances in Social Sciences Research Journal, 2021)
Many global organizations today have shown tremendous growth year after year and the measure of their success is beyond what the competition has achieve. The most common characteristic of the globally successful organizations is their continuous engagement in innovation that not only changes the playing field in the competition, but also creates a disruption in which the influence of the innovation impact social, economic, and political dynamics of the modern world. Facilitating innovation requires strategic approach by organizations in the processes of implementation. Some of the key characteristics of an organization that successfully facilitates the innovation process includes flexibility, openness, agility, adaptiveness, and cultivation. In the case of Oman, facilitating innovation and strategically applying the techniques to achieving positive outcome is a challenge that organizations are striving to overcome. Notable examples of innovation process approach by Omani organizations include creating a network of other organizations that are willing to partake in information exchange. Another example is collaboration in which a less capable organization collaborate with larger firms creating a mutually beneficial partnership to facilitate innovation and development.